PEMANFAATAN FLAVONOID EKSTRAK DAUN KATUK (Sauropus androgynus (L) Merr) SEBAGAI ANTIOKSIDAN PADA MINYAK KELAPA - Indah Cikita, Ika Herawati Hasibuan, Rosdanelli Hasibuan (Universitas Sumatera Utara, 2016)
In this research, the katuk leaves (Sauropus androgynus (L) Merr) extracted for get flavonoid which used as antioxidant for the coconut oil. This research aims to determine the effect of the extraction time, the volume of the solvent, and the type of solvent for the yield and total flavonoid concentration of the katuk leaves extract and then to determine the effect of total flavonoid concentration and contact time the flavonoid of katuk leaves extract as antioxidants in coconut oil. The process used is extraction of katuk leaves used the solvent such as ethanol, n-heksana and etil asetat then extract will be analysed the yield and total flavonoid concentration of the katuk leaves extract. Then extract with the total flavonoid concentration 6,668%, 7,748% and 27,909% was used as a sample and contacted in the coconut oil with the contact time of 2, 4 and 6 days. Then, analysis is done of the coconut oil is the acid number, the iodine number and the peroxide number. The result obtained in this research is the best extraction time of 6 hours with solvent volume of 1250 ml with the best type of solvent is ethanol, the yield of extract is 0,243% and total flavonoid concentration is 27,909%. The total flavonoid concentration increasing cause a decrease the acid number, the iodine number increase and decrease the peroxide number which proved that katuk leaves extract can be used as antioxidants in the coconut oil with the best result is the total flavonoid concentration in 27,909% where the acid number is 0,962 mg KOH/g, the iodine number is 38,705 g I2/100 g and the peroxide number is 13,333 Meq/kg. The contact time of flavonoid in the coconut oil which increasing cause oil properties is getting worse but the results are better than the oil without the addition of extract.